2015
DOI: 10.1155/2015/176582
|View full text |Cite
|
Sign up to set email alerts
|

Activity ofα1-Antitrypsin and Some Lysosomal Enzymes in the Blood Serum of Patients with Chronic Obstructive Pulmonary Disease after Smoking Cessation

Abstract: The activity of α 1-antitrypsin (AAT) and the lysosomal enzymes, cathepsin D (CTS D), arylsulfatase (ASA), and acid phosphatase, (AcP) was determined in patients with COPD (GOLD category A). Moreover, the diagnostic usefulness of these parameters in blood serum was assessed along with establishing whether smoking cessation affects these parameters. The study included 70 patients with COPD who ceased smoking (study group) and two control groups of 33 subjects each: nonsmokers without COPD (control I) and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Poor lifestyle preferences can contribute to the risk of COPD infection, and smoking is a common risk factor. Nicotine and other components in cigarettes can damage lung tissue, which may lead to pulmonary fibrosis, thereby affecting lung function, and significantly increasing the prevalence of COPD [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor lifestyle preferences can contribute to the risk of COPD infection, and smoking is a common risk factor. Nicotine and other components in cigarettes can damage lung tissue, which may lead to pulmonary fibrosis, thereby affecting lung function, and significantly increasing the prevalence of COPD [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal enzymes, in small amounts, constantly leak from lysosomes into the extracellular space and then into the blood. This increased release may, in be selective and may indicate tissue remodeling and/or pathological processes [34]. The present study demonstrated a positive correlation between serum activities of CTS D and ASA in cataract patients (r = 0.43, p = 0.039; Figure 3A) and between serum activities of AcP and ASA in healthy controls (r = 0.35, p = 0.046; Figure 3B), which may suggest the nonselective permeation of enzymes from lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that short-term CWI used as a postexercise regeneration method did not damage the lysosomal membranes and lysosomal enzymes did not enter the bloodstream. It has been proven that lysosomal enzymes are involved in the formation of post-exercise damage to muscle cells [ 72 , 73 ]. Exercise causes greater oxygen consumption by the mitochondria, leading to increased formation of ROS, which results in peroxidation of the muscle cell membrane.…”
Section: Discussionmentioning
confidence: 99%